Formulation of oral gel containing Baccaurea angulata fruit extract for wound healing of tooth extraction - Mohammad Nasrin bin Abdul Rahman (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2018)
This study investigated the potential of different gelling agents to be developed as dental gel formulation of Baccaurea angulata fruit extract as well as the effect of B. angulata fruit extract towards wound healing at tooth extractions sites. Since wound healing process is interrupted in diabetic patient, a well characterised and optimized B. angulata dental gel is believed to have the potential in promoting the healing process due to its high antioxidant content. Rheological properties of 24 different gelling agents were screened, then the best gelling agents were further evaluated for their spreadability, texture profile analysis, and their release profiles using Franz cell diffusion to identify best formulation for in vivo study. In in vivo study, the dental gels were applied in the alveolar socket after tooth extraction in diabetic rats. Diabetic was induced using Streptozotocin, and their left mandibular first molar teeth were extracted. Rats were divided into 6 groups (diabetic rats applied with plain gel, alveolex, 3%, 5%, and 10% Baccaurea angulata extract respectively). Group 6 were non diabetic rats applied with plain gel. The detailed rheological profiles of each of the 24 different gels were successfully documented. Guar gum, konjac gum and carbopol were found to be among the best candidates for B. angulata dental gel. The Franz cell study had found that 4% carbopol gel had the best release profile in finite an infinite dosing. Regarding in vivo study, it was found that B. angulata significantly promoted tooth extraction wound healing in diabetic rats comparable to diabetic group treated with alveolex and non-diabetic rats at early phase of the wound. However the positive effect were not obvious at day 7, while at day 18, groups treated with B. angulata had better mean scores in most wound healing parameters (e.g. presence of fibroblast, collagen fibres and epithelization) although not statistically significant different. B. angulata dental gel was found to have the best positive effects on wound healing. As a conclusion, B. angulata fruit extract promotes tooth extraction wound healing in diabetic rats during some stages of the wound healing process. This study also explored the rheological properties of different gelling polymers thus contributing towards their application in pharmaceutical technology and industry. Besides, the potential of B. angulata wound healing activity will open up new possibilities in promoting the wound healing in diabetic patient.